2015
DOI: 10.1093/eurheartj/ehv450
|View full text |Cite
|
Sign up to set email alerts
|

Management strategies in patients affected by chronic total occlusions: results from the Italian Registry of Chronic Total Occlusions

Abstract: Our data showed how CTO PCI might significantly improve the survival and decrease MACCE occurrence at 1 year follow-up in comparison with MT and/or CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
125
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(144 citation statements)
references
References 29 publications
9
125
1
9
Order By: Relevance
“…CTOs have received this attention because they are prevalent among patients with coronary artery disease [1][2][3][4][5] and are present in as many as 10% to 20% of all patients referred for diagnostic angiography. 6,7 However, PCI success rates for CTO have been demonstrated in earlier studies to be only in the 60% to 70% range, 8 although some centers have reported success rates >80%.9-11 Nevertheless, these rates are considerably lower than the rates for nonoccluded lesions, 2,8,12 and there is much controversy about the importance of performing CTO PCI. 13 Furthermore, little is known about the use of CTO in population-based regions and about regional hospital practice pattern variations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CTOs have received this attention because they are prevalent among patients with coronary artery disease [1][2][3][4][5] and are present in as many as 10% to 20% of all patients referred for diagnostic angiography. 6,7 However, PCI success rates for CTO have been demonstrated in earlier studies to be only in the 60% to 70% range, 8 although some centers have reported success rates >80%.9-11 Nevertheless, these rates are considerably lower than the rates for nonoccluded lesions, 2,8,12 and there is much controversy about the importance of performing CTO PCI. 13 Furthermore, little is known about the use of CTO in population-based regions and about regional hospital practice pattern variations.…”
mentioning
confidence: 99%
“…CTOs have received this attention because they are prevalent among patients with coronary artery disease [1][2][3][4][5] and are present in as many as 10% to 20% of all patients referred for diagnostic angiography. 6,7 However, PCI success rates for CTO have been demonstrated in earlier studies to be only in the 60% to 70% range, 8 although some centers have reported success rates >80%.…”
mentioning
confidence: 99%
“…Tomasello et al9 examined the long‐term outcomes of 1777 CTO patients from the Italian CTO Registry, according to treatment strategy: PCI, 43.7%; medical therapy, 46.5%; or surgery, 9.8%. At 1‐year follow‐up, the incidence of cardiac death (1.4% versus 4.7% versus 6.3%; P <0.001) and major adverse cardiac events (MACEs) (2.6% versus 8.2% and 6.9%; P <0.001) were significantly lower in the PCI group.…”
Section: Clinical Benefitsmentioning
confidence: 99%
“…8,9 In general, several registries have shown promising results on the clinical benefits of CTO PCI in wideranging populations, but these data are still affected by some confounders (ie, higher comorbidities burden of medically treated patients) to drive effective indications change. 10 Medical and Invasive Approaches) trial assessing the impact of an invasive strategy versus optimal medical therapy in patients with moderate to severe ischemia will provide new important insights on optimal patient selection for CTO recanalization. Although we are waiting for additional more conclusive studies, if a CTO revascularization is indicated based on a careful clinical evaluation, there is overall supportive evidence to choose PCI.…”
Section: See Article By Karmpaliotis Et Almentioning
confidence: 99%